Cross-Cultural Communication Adaptation: Adjusting Speaking Habits for Migrant Students in Makassar City - Murtadir, Nur Fadhilah; Najamuddin; Alimin Alwi (Cita konsultindo, 2026)
The increasing number of students from other regions enrolling in universities makes it very important for us to understand the social and cultural barriers that students experience when adjusting to a new environment. The challenge faced by these migrant students is how to adapt to cultural variations in communicating with other students at Makassar State University. The purpose of this study is to examine intercultural communication, adaptability, and the role of digital communication among migrant students. This research uses a qualitative ethnographic communication study method. The findings of this study reveal that there are significant differences with the culture they encounter, including differences in language, attitude, and strong intonation when speaking that differ from the students' regions of origin, cultural values, and the use of digital communication such as articles, social media content, journals, and websites, which play a role in their adaptation. Another thing that overseas students do in facing challenges in communicating and adapting to new cultures is to observe, learn, and then begin to accept other cultures by adopting their attitudes, principles, and habits. This is known as acculturation.